Явление вырождения как скрытая актуальная проблема современной социокультурной реальности - Фёдоров, Ю.В. (Культура народов Причерноморья, 2013)
Стаття присвячена проблеми сучасного соціуму XXI сторіччя - феномену виродження. Це
явище соціокультурної реальності наших днів розглядається в контексті антропологічної кризи
сучасної техногенної цивілізації. Аналіз несприятливої цивілізаційної ситуації в біологічному
(генетичному) і соціокультурному аспектах спрямований на необхідність пошуку шляхів виходу з
сучасної антропологічної кризи з найменшими втратами. Статья посвящена обострившейся проблеме современного социума XXI столетия –
феномену вырождения. Это явление социокультурной реальности наших дней рассматривается в
контексте антропологического кризиса современной техногенной цивилизации. Анализ неблагоприятной
цивилизационной ситуации в биологическом (генетическом) и социокультурном аспектах направлен на
необходимость поиска путей выхода из современного антропологического кризиса с наименьшими
потерями. The article is devoted to the aggravated problem of modern society of XXI century - the
phenomenon of degeneration. This phenomenon of socio-cultural reality of our days is considered in the context
of anthropological crisis of modern industrial civilization. Analysis of the unfavorable situation of civilization in
a biological (genetic) and socio-cultural aspects aimed at the need to find a way out of the contemporary
anthropological crisis with minimal losses.
Value orientations, basic moral principles that prevailed in the world of the last few centuries, found its
antinomy. Mankind in a conflict for the first time to the beginning of the third millennium and has to re- set, but
in a global, general historical basis was "eternal" questions of existence - of the meaning of existence, the nature
of man, his cultural- historical mission, to develop new criteria for true and imaginary, the beautiful and the
ugly, the healthy and the sick .
The phenomenon of degeneration because of its many aspects is a great way to multi-disciplinary research,
including both biologically oriented, psychopathological and philosophical, cultural exploration, as well as to
address the fundamental socio-cultural issues, including those related to the evolution of individual and social
identity. A comparative - historical and cross-cultural research on the human psyche and the culture of
sexology. We need a serious study parafilnyh forms of human behavior and the reflection of these forms in
different manifestation of the creative acts.
The phenomenon of degeneration as complex as the phenomenon of the man himsel, and degeneralogiya a
complex science, located at the intersection of many scientific knowledge about man only crystallizes and is in
dire need of comprehensive scientific and fundamental justification. Only philosophy can most holistic and
deeply understand the giant reservoir particular scientific knowledge about the phenomenon of degeneration of
man and give a universal answer to many specific issues and develop strategies to overcome theт.